(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: This research was conducted to estimate the activity concentration level of 40K, 238U and 232Th in soil and cassava and determine the transfer factor from soil to cassava in Ughelli North, Delta State, Nigeria. Materials and Methods: These were examined using gamma spectrometry and considering a lead-shielded 3 x 3inch coaxial type Sodium Iodide Thallium doped detector. Results: The mean activity concentrations of 40K, 238U and 232Th are 45.49 ± 4.28 BqKg−1, 3.15 ± 0.77 BqKg−1 and 0.56 ± 0.06 BqKg−1 respectively in soil samples and 134.08 ± 11.59 BqKg−1, 3.89 ± 0.93 BqKg−1 and 0.81 ± 0.09 BqKg−1 correspondingly in cassava samples. The mean transfer factor of 40K, 238U and 232Th from soil to cassava are 3.44 ± 0.75, 1.94 ± 0.32 and 1.34 ± 0.54 respectively. Peak values of the TF were noted as 8.52 for 40K at U18, D18, 25.58 for 238U at U12, D12 and 5.71 for 232Th at U11, D11. Conclusion: The activity concentration of 40K, 238U and 232Th in the area are lower than the world average values. Consequently, it will not pose any radiological hazard if consumed. The high value of Transfer factor is attributed to the richness of the organic matter in the soil and may indicate high ability to transfer radionuclides in the soil to food crops but from the concentration information, these radionuclides present in the soil are low as well as annual effective doses. There is no radiological risk of ingestion.